Implementasi Algoritma Multiplicative Random Number Generation (MRNG) Dalam Menemukan Objek Pada Game Berbasis Android - Muhammad Fauzy; Tommy; Imran Lubis (SNASTIKOM, 2022)
Games are a form of entertainment enjoyed by all age groups of children, adults and the elderly. This researchwill build a game to find a simple game object that is played by disassembling an object or image. Randomizedimages require an algorithm so that it can be applied to games, Game finds the process of playing randomizedobjects using the algorithm used in this study, namely Multiplicative Random Number Generation (MRNG) whichis an algorithm to be able to sequentially or sequence numbers as the results of calculations with a computerwhose distribution is known so that the numbers appear randomly and are used continuously. The result of thisresearch is an android-based game in which there is an object-finding game that utilizes Multiplicative RandomNumber Generation (MRNG). In this study, it was developed using Unity 3D software and utilizing the assets ofUnity 3D software with a visual code text editor, in modeling the flow diagrams in this study using a unifiedmodeling language. The purpose of this research is to produce games that can hone thinking skills and build gamesto find objects. using multiplicative random number generation algorithm. This game can be played by all peoplein training memory and thinking skills, this game is equipped with a time feature.